Differences between the Influence of Observing One’s Own Movements and Those of Others in Patients with Stroke - Takeshi Fuchigami; Shu Morioka (Stroke Research and Treatment)
We aimed to investigate differences between the influence of observing one’s own actions and those of others in patients with stroke with hemiplegia. Thirty-four patients with stroke who had experienced a right or left hemispheric lesion (RHL: n = 17; LHL: n = 17) participated in this study. Participants viewed video clips (0.5× speed) of their own stepping movements (SO) as well as those of others (OO). After viewing the video clips, participants were asked to evaluate the vividness of the mental image of the observed stepping movement using a five-point scale, in accordance with that utilized in the Kinesthetic and Visual Imagery Questionnaire (KVIQ). We also examined changes in imagery and execution times following action observation. When all patients were considered, there were no significant differences between SO and OO conditions. However, in the RHL subgroup, KVIQ kinesthetic subscore and changes in imagery and execution times were greater in the OO condition than in the SO condition. In the LHL subgroup, changes in imagery times were greater in the SO condition than in the OO condition. These findings indicated that viewing the movements of others led to more vivid imagery and alteration in performance in patients with right-sided stroke, when compared to viewing one’s own movements. Therefore, the present study suggests that clinicians should consider the side of the damaged hemisphere when implementing action observation therapy for patients with stroke.